Analysis of semantic universality and uniqueness of phraseological units in the language of Ahmad Hamdi Tanpinar (Eurasian Journal of Philology Science and Education, 2019)
In the article the universal and uniqueness peculiarities of the phraseological units in A.Tanpinar’s works drawing attention with the manifestation of the ability to use language units in the creativity with a particular skill are analyzed. The coincidence of contradictory facts in the development of frazeologisms, which have the particular interest in the language of the author, is the fact that, in addition to the functional units of modern language, lexemes that have lost their functionality and it is one of the factors that demonstrate the relevance of linguistic investigation of Tanpinar’s works. Though some of these frazeologisms are of particular interest as bearer of national and ethical factors, both in terms of their structural and semantic views, while the other ones are interested in conformity with the frazeologisms found in different languages. Analyzing the frazeologisms used in the artistic works in this way also allows them to observe their peculiarities of forming and functionality in the language. The linguistic analysis of Tanpınar’s works shows that the universality in phrazeological units can usually be related to the origin of language from the same source or to the acquisition of traces of mutual contact with other languages historically. Both cases are justified as the cause of the universality of frazeologisms used in the author’s works. Uniqueness in the phrazeological units can be formed by both linguistic and extra-linguistic factors. As all the facts about the way of life and the way of thinking are based on the phrazeological unit, as well as the social factors affect the development tendencies of the language, the existence of frazeologisms is remarkable in every language.